Learned helplessness a theory for the age of personal control - Peterson, Christopher; Maier, Steven F.; Seligman, Martin E. P. 1942- (Oxford Univ. Press, 1993)
When experience with uncontrollable events gives rise to the expectation that events in the future will also elude control, disruptions in motivation, emotion, and learning may ensue. "Learned helplessness" refers to the problems that arise in the wake of uncontrollability. First described in the 1960's among laboratory animals, learned helplessness has since been applied to a variety of human problems entailing inappropriate passivity and demoralization. While learned helplessness is best known as an explanation of depression, studies with both people and animals have mapped out the cognitive and biological aspects. The present volume summarizes and integrates the theory, research, and application of learned helplessness. Each line of work is evaluated critically in terms of what is and is not known, and future directions are sketched.
Keywords: Aangeleerde hulpeloosheid; Contrôle (psychologie); Contrôle interne/externe (Personnalité); Détresse; Locus of control; Psychopathologie; Résignation apprise; Helplessness (Psychology); Helplessness, Learned; Internal-External Control; Psychology, Pathological; Psychopathology; Gelernte Hilflosigkeit